Comparison of Pollution Level at Jangkok River Estuary and Ancar River Estuary Using Periphyton Bioindicators - Syamsul Bahri; Priyo Hartanto; Anak Agung Ayu Diah Kusumadewi; Bung Ashabul Kahfi; Halimatusa'adiah (Postgraduate, University of Mataram, 2023)
Water quality can be determined using various parameters such as physical, chemical and biological parameters. In this study, researchers used biological parameters, namely using periphyton organisms as bioindicators of water pollution. The aims of this study were to determine the abundance and diversity index of periphyton species in the Jangkok and Ancar rivers, to determine the periphyton species found in the Jangkok and Ancar rivers, and to determine the water quality of the Jangkok and Ancar rivers based on periphyton bioindicators. Sampling was only at the mouth/downstream of the Jangkok and Ancar rivers. Periphyton sampling at each location was carried out three times in the downstream part of the river. The division is located on the right, middle and left bank of the river body. At each of the three sample locations, 1 sample of the substrate will be taken, namely in the form of stones submerged under the surface of the river water, so that the total samples taken are 9 samples. The data obtained then calculated the Abundance Value and Diversity Index in order to get a value in determining the Quality of River Pollution. Periphyton abundance values ​​in the Jangkok and Ancar rivers were 30,116 and 4,948 cells/cm2, then the periphyton species diversity index in the Jangkok and Ancar rivers were 2,021 and 2,329. The temperature values ​​obtained at both locations ranged from 22-25 0C with a pH ranging from 7.8-8.3. The water quality of the Jangkok River and Ancar River is based on the index value of species diversity, including in the category of light pollution/unpolluted which means that fertility can be utilized. So that people need to keep paying attention to the cleanliness of the environment for the sake of survival in the future